Shape graphs and the instantaneous inference of tactical positions in soccer - Ulrik Brandes; Hadi Sotudeh; Doğan Parlak; Paolo Laffranchi; Mert Erkul (npj Complexity)
Abstract We propose shape graphs as instantaneous representations of spatial arrangements in association football (soccer). Shape graphs are a novel type of subgraph of Delaunay triangulations inspired by related applications in fingerprinting and facial expression detection. They provide a foundational data structure that supports various downstream tasks in a manner that is flexible, explainable, and efficient. While previous approaches aggregate spatial positions over periods of time to stabilize the underlying signal, we instead interpret each frame individually for increased explainability at the highest possible temporal resolution. As an example use case we introduce position plots, a novel visualization capturing the characteristic fluidity of relative positioning during a game while retaining the possibility to add match context.